The experience of Thai adolescents with depression: A qualitative study - Chuntana Reangsing; Khanittha Pitchalard; Katemanee Moonpanane; Pawadee Wimolphan (Wiley, 2024)
Abstract Aim People who have depression experience a maelstrom of emotion as they attempt to understand what is happening to them. While the experience has been quite extensively documented in adults and older individuals, there is a great deal less information available about adolescent depression experiences and reactions. The purpose of this study was to investigate the experiences of Thai‐adolescents suffering from depression. Design Interpretative phenomenological analysis. Method Fourteen adolescents were recruited from a secondary school in Chiangrai province, Thailand. Semi‐structured interviews were carried out. Interviews were analysed using interpretative phenomenological analysis. Results The following four themes were identified: (1) struggling to make sense of their situation, (2) feeling down and withdrawing, (3) contemplating self‐harm and (4) therapy as a last choice. The results point to the continuing significance of promoting psychoeducation for Thai‐adolescents with depression as well as parents, school nurses and health providers while eliminating stigma.